2009
DOI: 10.2337/db09-1159
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Interleukin-1β and Tumor Necrosis Factor-α Regulate Different Transcriptional and Alternative Splicing Networks in Primary β-Cells

Abstract: OBJECTIVECytokines contribute to pancreatic β-cell death in type 1 diabetes. This effect is mediated by complex gene networks that remain to be characterized. We presently utilized array analysis to define the global expression pattern of genes, including spliced variants, modified by the cytokines interleukin (IL)-1β + interferon (IFN)-γ and tumor necrosis factor (TNF)-α + IFN-γ in primary rat β-cells.RESEARCH DESIGN AND METHODSFluorescence-activated cell sorter–purified rat β-cells were exposed to IL-1β + IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
137
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(160 citation statements)
references
References 49 publications
16
137
1
6
Order By: Relevance
“…7g, h). We have previously shown that IRF-7 plays an important role in the regulation of chemokine expression by TNF-α+IFN-γ [42], but this does not explain the present observations, as STAT1 KD decreased IRF-7 expression (ESM Fig. 4b).…”
Section: Il-17a Exacerbates Cytokine-induced Apoptosis In Rat Ins-1e contrasting
confidence: 90%
See 1 more Smart Citation
“…7g, h). We have previously shown that IRF-7 plays an important role in the regulation of chemokine expression by TNF-α+IFN-γ [42], but this does not explain the present observations, as STAT1 KD decreased IRF-7 expression (ESM Fig. 4b).…”
Section: Il-17a Exacerbates Cytokine-induced Apoptosis In Rat Ins-1e contrasting
confidence: 90%
“…The chemokine 'signature' of pancreatic islets seems to vary depending on the cytokine stimulus provided. For instance, the pattern of chemokines induced by IL-1β+IFN-γ in pancreatic beta cells is markedly different from that induced by TNF-α+IFN-γ [42]. We showed here that IL-17A alone induces a mild increase in expression of CXCL1, CXCL8, CCL2 and CCL20, in addition to its stimulatory effect on human islets exposed to IL-1β+IFN-γ and TNF-α+IFN-γ.…”
Section: Discussionmentioning
confidence: 61%
“…In order to obtain a broader evaluation of the impact of cytokine exposure on primary human or rodent islet cells, we made a global comparison of cytokine-modulated gene expression in human and mouse islets, and in FACS-purified rat beta cells based on previously published microarray and RNA sequencing data [17,[42][43][44][45]. There was an overall higher ranking similarity between human and mouse gene expression than between human and rat gene expression for both up-and downregulated genes (ESM Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This was previously shown to be mediated by TNF-a-induced IRF-7 expression. 44 As CHOP modulates IRF-7 expression, the observed effects of CHOP KD on the expression of these chemokines probably occur through the combined decreased activity of NF-kB and IRF-7. These data strongly suggest that CHOP contributes to inflammation.…”
Section: Discussionmentioning
confidence: 99%